Output-feedback protocols without controller interaction for consensus of homogeneous multi-agent systems: A unified robust control view - Li, Xianwei (2017)
This paper investigates the consensus problem of homogeneous linear multi-agent systems using output feedback. An observer-type protocol is formulated, which only requires the relative output information of neighbours and does not require information exchange between controllers. It is shown that the protocol bridges some existing ones of the same nature. A robust control approach is presented for consensus protocol design, which requires one to solve a Riccati equation and a linear matrix inequality. Dual results are also discussed. By virtue of low- and high-gain techniques, it is shown that certain solvability conditions are to be satisfied to achieve consensus for agents that are not exponentially unstable or are minimum-phase, leading to a unified point of view for some existing results. A numerical example is provided to illustrate the advantages of the proposed design method.